2018
DOI: 10.1186/s13071-018-2906-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation and the protective immunity evaluation of Eimeria maxima surface antigen gene

Abstract: BackgroundCoccidiosis is recognised as a major parasitic disease in chickens. Eimeria maxima is considered as a highly immunoprotective species within the Eimeria spp. family that infects chickens. In the present research, the surface antigen gene of E. maxima (EmSAG) was cloned, and the ability of EmSAG to stimulate protection against E. maxima was evaluated.MethodsProkaryotic and eukaryotic plasmids expressing EmSAG were constructed. The EmSAG transcription and expression in vivo was performed based on the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
(63 reference statements)
3
16
0
1
Order By: Relevance
“…The reduction in oocyst production was 30–90% using E. tenella or E. acervulina antigens in recombinant protein, DNA or live-vector formulations with or without cytokines as adjuvants [27, 28]. Moreover, the protection against E. tenella , E. necatrix , E. maxima or E. acervulina infection was also reported to be enhanced using multivalent epitope DNA vaccines from multiple antigens compared to a single antigen [2934]. Although those subunit or recombinant vaccines achieved promising successes in the laboratory and are much safer and less expensive than live anticoccidial vaccines, no large-scale trials have been reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in oocyst production was 30–90% using E. tenella or E. acervulina antigens in recombinant protein, DNA or live-vector formulations with or without cytokines as adjuvants [27, 28]. Moreover, the protection against E. tenella , E. necatrix , E. maxima or E. acervulina infection was also reported to be enhanced using multivalent epitope DNA vaccines from multiple antigens compared to a single antigen [2934]. Although those subunit or recombinant vaccines achieved promising successes in the laboratory and are much safer and less expensive than live anticoccidial vaccines, no large-scale trials have been reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of Eimeria spp. proteins have shown that a similar effect can be produced after immunization with recombinant protein or recombinant plasmid [ 25 , 26 ]. The data presented here showed that immunization with r Et CHP18905 could produce partial protection against live E. tenella infection.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of soluble sCD4 and sCD8 in serum is consistent with the number of CD4+and CD8+lymphocytes that produce them [ 41 , 46 ]. Previous studies reported that levels of sCD4 and sCD8 were higher in experimental groups immunized with r Em SAG and r Em MIC7 compared with the control [ 16 , 26 ]. However, the results presented here showed that serum sCD4 and sCD8 were not significantly different in immunized chickens compared to non-immunized controls.…”
Section: Discussionmentioning
confidence: 99%
“…The immunofluorescence assay was performed as previously described with several improvements ( Liu et al., 2018 ). Briefly, the purified sporozoites and merozoites were adhered to coverslips precoated with poly-lysine, fixed with 4% (w/v) paraformaldehyde, and permeabilized with 0.1% Triton.…”
Section: Methodsmentioning
confidence: 99%